Engagement of monocytes, NK cells, and CD4+ Th1 cells by ALVAC-SIV vaccination results in a decreased risk of SIVmac251 vaginal acquisition. - Giacomo Gorini; Slim Fourati; Monica Vaccari; Mohammad Arif Rahman; Shari N Gordon; Dallas R Brown; Lynn Law; Jean Chang; Richard Green; Fredrik Barrenäs; Namal P M Liyanage; Melvin N Doster; et al. (PLoS Pathogens, 2020)
The recombinant Canarypox ALVAC-HIV/gp120/alum vaccine regimen was the first to significantly decrease the risk of HIV acquisition in humans, with equal effectiveness in both males and females. Similarly, an equivalent SIV-based ALVAC vaccine regimen decreased the risk of virus acquisition in Indian rhesus macaques of both sexes following intrarectal exposure to low doses of SIVmac251. Here, we demonstrate that the ALVAC-SIV/gp120/alum vaccine is also efficacious in female Chinese rhesus macaques following intravaginal exposure to low doses of SIVmac251 and we confirm that CD14+ classical monocytes are a strong correlate of decreased risk of virus acquisition. Furthermore, we demonstrate that the frequency of CD14+ cells and/or their gene expression correlates with blood Type 1 CD4+ T helper cells, α4β7+ plasmablasts, and vaginal cytocidal NKG2A+ cells. To better understand the correlate of protection, we contrasted the ALVAC-SIV vaccine with a NYVAC-based SIV/gp120 regimen that used the identical immunogen. We found that NYVAC-SIV induced higher immune activation via CD4+Ki67+CD38+ and CD4+Ki67+α4β7+ T cells, higher SIV envelope-specific IFN-γ producing cells, equivalent ADCC, and did not decrease the risk of SIVmac251 acquisition. Using the systems biology approach, we demonstrate that specific expression profiles of plasmablasts, NKG2A+ cells, and monocytes elicited by the ALVAC-based regimen correlated with decreased risk of virus acquisition.